Unilateral vocal cord paralysis due to anatomical variation of recurrent laryngeal nerve injury during thyroid surgery: how to manage? - Nur Izzati Ishak; M.M. Baki; R. Muhammad (2020)
A case of hoarseness and fluid aspirations immediate post thyroid surgery in a 74-year-old female is reported. She has multinodular goitre and underwent total thyroidectomy and there was sudden loss of nerve monitoring signal intraoperatively during dissection of the respective thyroid pole. Further dissection showed that the entrance of recurrent laryngeal nerve (RLN) was abnormal. She was anticipated to have RLN injury and with some symptoms, she was referred to an otolaryngologist and found to have unilateral vocal fold paralysis (UVFP). Injection laryngoplasty was performed to alleviate the acute symptoms and she was fully recovered within 6 months from the temporary UVFP.